PENGARUH PERMAINAN MOBIL KATA TERHADAP KETERAMPILAN MEMBACA PERMULAAN ANAK DI TAMAN KANAK-KANAK QATRINNADA KOTA PADANG - Sewarna Indah; Yulsyofriend (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to determine the effect of word car games on children's early reading skills at Qatrinnada Kindergarten, Padang City. This research is a type of quantitative research with experimental methods. The samples were B2 and B3 grade children, which served as experimental and control classes with each class totaling 15 children. The data collection techniques in this study were using tests and observations. And for data analysis techniques carried out through normality tests, homogeneity tests and hypothesis tests. The results of data analysis showed that the average score of the experimental class pre-test was 24.60 and the post-test was 26.26. While the average score of the control class pre-test was 22.46 and the post-test was 23.53. Based on the results of the hypothesis test, it shows that the sig value (2-tailed) is 0.003 <0.05, so it can be concluded that the word car game has an effect on children's reading skills at Qatrinnada Kindergarten, Padang City.